Keanekaragaman Serangga di Perkebunan Kakao Desa Kawalo Kecamatan Taliabu Barat Kabupaten Pulau Taliabu - Duwila, Ila; Karim, Wahyudin Abdul; Anggo, Sulasmi; Lige, Firga Nabila (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2023)
Abstract: Cocoa is biodiversity that must be preserved. In addition, cocoa is one of the main pillars of the plantation area which plays an important role in the community's economy. Meanwhile, insects are part of biodiversity with the ultimate goal of increasing cocoa productivity. Insects are organisms that harm plants, especially cocoa. The purpose of this research is to determine the types of insects found in the Cocoa Plantation of Kawalo Village, West Taliabu District, Taliabu Island Regency.Â The type of research used is descriptive quantitative. This research was conducted in June-July 2022 By using a purposive sampling method or deliberately determining as many as 9 points with an area of 1 Ha with the sampling technique using the Yellow trap method. Based on the results of research from 9 traps conducted in Kawalo Village, Taliabu Barat District, Taliabu Island Regency, it found that 49 individuals from 11 insect species, including Amata aperta, Bactrocera dorsalis, Colletidae, Euagoras plagiatus, Herpetogramma licarsisalis, Megachile plut, Nisotra bicolorata, Oechopila smaragdina, Riptortus linearis, Sphaeroderma testaceum, Telostylinus lineolatus. Insect Diversity Index found results using the Shannon-Wienner Index, namely the variety of H' (1.78611) in the medium category. It's because the location of the Kawalo Village Cocoa Plantation is visited by the community almost every day, and those who visit the cocoa plantation often do pruning of the cocoa tree which causes disturbance to insect activity. On environmental factors obtained in the morning taken at 08.00 WITA with temperature (29.2), humidity (60%) in the afternoon taken at 17.00 WITA with temperature (30.00), humidity (61%).